Parents' perception of children's fear: from FSSC-IT to FSSC-PP - Salcuni, Silvia; Dazzi, Carla; Mannarini, Stefania; Di Riso, Daniela; Delvecchio, Elisa (Frontiers in Psychology, 2015)
Studies involving parents’ reports about children’s fears and multiple informant comparisons are less extended than investigations on children’s self-reporting fear schedules. Starting with the Italian version of FSSC-R, the FSSC-IT, the main aims of this study were to adapt a schedule for parents’ perception of their children’s fear: the FSSC-Parent Perception. Its psychometric properties were examined in a large sample of parents (N=2970) of children aged 8 to 10 years. Exploratory and confirmatory factorial structures were examined and compared with the Italian children’s ones. Mother versus father, children’s gender and school age group effects were analyzed. The confirmatory factor analysis confirmed a four correlated factors solution model (Fear of Danger and Death; Fear of Injury and Animals; Fear of Failure and Criticism; Fear of the unknown and Phobic aspects). Some effects related to child gender, age group, mother versus father, were found. The FSSC-PP properties supported its use by parents to assess their children’s fears. A qualitative analysis of the top 10 fears most endorsed by parents will be presented and compared with children’s fears. Clinical implications about the quality of parent-child relationships where discussed, comparing mothers and fathers, and parents’ perception about daughters’ and sons’ most endorsed fears.